Fractal dimension and magnetic susceptibility of magnetically labelled biosorbent based on saccharomyces cerevisiae yeast - Gorobets, S.V.; Gorobets, O.Yu.; Kovalyov, O.V.; Sopina, A.V.; Chyzh, Yu.M.; Cherepov, S.V. (Functional Materials, 2015)
The magnetic susceptibility and fractal dimension of the modified magnetically labelled biosorbent based on Saccharomyces cerevisiae yeast, obtained by magnetohydrodynamic method of mixing the yeast suspension with nano-magnetite particles, were studied. It was established that the surface structure and stability of magnetic susceptibility of magnetically labelled biosorbent change with the change of its fractal dimension.